2021
DOI: 10.1186/s13756-021-01012-8
|View full text |Cite
|
Sign up to set email alerts
|

ESBL/pAmpC-producing Escherichia coli and Klebsiella pneumoniae carriage among veterinary healthcare workers in the Netherlands

Abstract: Background Animals are a reservoir for ESBL/pAmpC-producing Escherichia coli/Klebsiella pneumoniae (ESBL-E/K). We investigated the association between occupational contact with different types of animals and the prevalence of ESBL-E/K carriage among veterinary healthcare workers, assessed molecular characteristics of ESBL-E/K, and followed-up on the ESBL-E/K carriage status of participants and their household members. Methods Participants completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Several studies have demonstrated that farm animals are a reservoir of ARB (such as E. coli , K. pneumonia , Salmonella , S. aureus , etc.) and ARGs ( Table 1 ), and people can be infected with ARB through close contact with farm animals ( Tomley and Shirley, 2009 ; Dierikx et al, 2013 ; McDaniel et al, 2014 ; Saliu et al, 2017 ; Founou et al, 2021 ; Meijs et al, 2021 ).…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated that farm animals are a reservoir of ARB (such as E. coli , K. pneumonia , Salmonella , S. aureus , etc.) and ARGs ( Table 1 ), and people can be infected with ARB through close contact with farm animals ( Tomley and Shirley, 2009 ; Dierikx et al, 2013 ; McDaniel et al, 2014 ; Saliu et al, 2017 ; Founou et al, 2021 ; Meijs et al, 2021 ).…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
“…The occurrence and prevalence of extended-spectrum β-lactamase (ESBL)- and AmpC β-lactamase (AmpC)-producing E. coli and K. pneumoniae in farmworkers and household members in Netherlands were investigated by Meijs et al (2021) . PCR and sequencing results showed that ESBL-producing E. coli and K. pneumoniae in workers accounted for 9.8%, higher than that in the Dutch population (5%), which may be related to direct contact with animals.…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The World Health Organization (WHO) has included third-generation cephalosporin-resistant E. coli and K. pneumoniae into the group of “critical pathogens” due to the increasing challenges for infection treatment, highlighting the importance of the monitoring and prevention of infections in humans and animals. In humans, Meijs et al (2021) have recently reported a high prevalence of fecal carriage of ESBL- E. coli and ESBL- K. pneumoniae in veterinary healthcare workers in the Netherlands compared to the general Dutch population (9.8% and 5%, respectively) ( Meijs et al, 2021 ). Likewise, in Dutch hospitals, the prevalence of ESBL- K. pneumoniae in 2020 increased up to 15% compared to 2019 (12%) ( NETMAP_MARAN, 2021 ).…”
Section: Discussionmentioning
confidence: 99%